2011
DOI: 10.1128/jvi.05259-11
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a Region of Hepatitis C Virus E2 That Is Responsible for Escape from Neutralizing Antibodies and a Core CD81-Binding Region That Does Not Tolerate Neutralization Escape Mutations

Abstract: Understanding the interaction between broadly neutralizing antibodies and their epitopes provides a basis for the rational design of a preventive hepatitis C virus (HCV) vaccine. CBH-2, HC-11, and HC-1 are representatives of antibodies to overlapping epitopes on E2 that mediate neutralization by blocking virus binding to CD81. To obtain insights into escape mechanisms, infectious cell culture virus, 2a HCVcc, was propagated under increasing concentrations of a neutralizing antibody to isolate escape mutants. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
147
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(155 citation statements)
references
References 42 publications
(70 reference statements)
7
147
1
Order By: Relevance
“…Broadly neutralizing human mAbs (bNAbs) capable of neutralizing diverse HCV strains have been isolated from HCV-infected individuals, proving that antibodies can target relatively conserved regions of the two HCV envelope glycoproteins (E1 and E2), despite the enormous genetic diversity of HCV (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Infusion of bNAbs is protective against infection in animal models of HCV (17,18), and a recent study also showed that bNAbs could abrogate established HCV infection in a humanized transgenic mouse model (19).…”
Section: Introductionmentioning
confidence: 99%
“…Broadly neutralizing human mAbs (bNAbs) capable of neutralizing diverse HCV strains have been isolated from HCV-infected individuals, proving that antibodies can target relatively conserved regions of the two HCV envelope glycoproteins (E1 and E2), despite the enormous genetic diversity of HCV (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Infusion of bNAbs is protective against infection in animal models of HCV (17,18), and a recent study also showed that bNAbs could abrogate established HCV infection in a humanized transgenic mouse model (19).…”
Section: Introductionmentioning
confidence: 99%
“…However, isolation of human mAbs capable of neutralizing multiple diverse HCV isolates has shown that nAbs may also target more conserved regions of the E1 and E2 proteins (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Discovery of these broadly neutralizing mAbs has raised hope that a vaccine inducing similar nAbs could prevent HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies to antigenic domain B share two contact residues at G530 and D535 (30,33,35), which are universally conserved and have been shown to participate in the interaction of E2 with CD81 (19,36). Some of the antigenic domain B epitopes also contain residues located within aa 434 to 446, e.g., an epitope identified by an antibody designated HC-11 (35,37 425 ) were synthesized using a C-terminal biotin residue with a Gly-Ser-Gly linker (American Peptide, Sunnyvale, CA).…”
mentioning
confidence: 99%